The Influence of Work Environment, Work Stress, and Work Discipline on Work Achievement - Tri Mulyani Kartini; Andrianto Prasetya Nugroho (Universitas KH. Abdul Chalim Mojokerto, 2025)
Success in building good governance in an agency is highly dependent on the support of quality human resources. The quality of human resources is directly proportional to the quality of work produced; the better the quality of human resources, the higher the quality of work achieved. This study aims to examine the effect of work environment, work stress, and work discipline on work achievement, with a focus on LAM Foundation employees in Dumai City. The method used in this research is quantitative, with the population consisting of employees of the foundation. Data processing was carried out using SmartPLS 3.0 software. The results showed that the t-statistic for the relationship between work environment and work achievement was 2.219 (greater than 1.96), and the p-value was 0.027 (less than 0.05). This indicates that the first hypothesis (H1), which states that the work environment has a positive effect on work achievement, is accepted. Furthermore, for the work stress variable, the t-statistic value is 2.267 (greater than 1.96) and the p-value is 0.024 (less than 0.05), which supports the second hypothesis (H2) that work stress also has a positive effect on work achievement. Finally, for work discipline, the t-statistic shows a value of 2.782 (greater than 1.96) with a p-value of 0.006 (less than 0.05), so the third hypothesis (H3), which states that work discipline has a positive effect on work achievement, is also accepted. Overall, work environment, work stress, and work discipline have a significant effect on work achievement, with a contribution of 69.9%.